Evaluation of corrosion resistance of commercial aluminum alloys in ethanol solutions - Kramer, Gustavo Raul (2018)
In the present research, we studied the corrosion resistance of commercial aluminum alloys exposed to ethanol produced in the northeastern region of Argentina and to commercial ethanol as reference medium. Electrochemical tests of potentiodynamic polarization and weight loss were performed by immersion at temperatures below the boiling point of ethanol (25 °C, 40 °C and 50 °C). The results showed that the increase in the corrosion rate of the alloys is directly proportional to the increase in the temperature of the solution, and that the combined action of contaminants in the alcohol (water, organic acids or aggressive ions) contributed to the increase in the aggressiveness of the environment. Specifically, through the results of the gravimetric tests, corrosion products characteristic of the formation of pitting corrosion and alkoxidation were observed. In contrast to the above, the existence of the pitting corrosion mechanism was demonstrated by defining a pitting potential in the potentiodynamic polarization curves.